PEMANFAATAN FITUR TRACK CHANGE PADA PERKULIAHAN EDITING DI PERGURUAN TINGGI - Eli Syarifah Aeni; Yusep Ahmadi F; Indra Permana (Jurnal Semantik, 2022)
In the current digital era, learning in every subject must be based on the use of Information and Technology (IT). It is not limited to lectures. The IT feature used in this research is the Track Change feature in Microsoft Word. The purpose of this research is to use the Track Change feature in lectures. The research method used is qualitative with a descriptive analysis approach. The subjects of this study were B2 class students, batch 2019 of the Indonesian Language and Literature Education Study Program, IKIP Siliwangi. The data are in the form of observations and questionnaires on student responses to manuscripts and the results of student edits. Through a problem-based editing model assisted by the Track Changes feature, students not only edit or edit simply, but every language error is edited and explained according to the error. The results showed that the use of the Track Changes feature in editing lectures went well. This is indicated by the data from observations on the activities of lecturers and students, student response questionnaires and the assessment of the results of editing student manuscripts.